Spatial Autocolleration and Economic Convergence in Lampung Province - Pratama, Ahmad Dhea; Suparta, I Wayan; Ratih, Arivia (JEJAK: Jurnal Ekonomi dan Kebijakan, 2022)
The regional economy is in space and time, space is an important strength in the activity of an economy. This study examines spatial dependencies in observing economic activity in the form of regions and the convergence hypothesis as a study to see the economic gap between poor and rich regions. The spatial interaction of the economy in this study uses the Moran I statistical method, LISA Signification, and LISA Clustered map, the Convergence Study is analyzed using ordinary least square panel data using the Fixed Effect model approach. This study uses secondary data and panel data with 15 districts and cities and the 2015-2019 time series. Testing Results spatial relationship between the GDP per capita 15 districts and cities in the province of Lampung year 2015-2019, there has been a positive spatial autocorrelation spatial pattern formation has a regional grouping of Economy with the indication of the same characteristics. A process of absolute convergence is marked and significant negative coefficient, an indication of speed- reducing the economic gap of 4.8%, so that the time required in a process of reducing the gap from the initial gap was 14.17 years in 15 districts and cities in the province of Lampung Year 2015-2019.